Pengaruh Bahan Ajar E-Modul Berpendekatan Contextual Teaching Learning Terhadap Peningkatan Kemampuan Pemahaman Konsep Peserta Didik - Yunia Lestari; Sugeng Sutiarso; Sugilar Sugilar (LPPM Universitas Terbuka, 2022)
The results of the observations show that there are no teaching materials in the form of e-modules used by mathematics teachers in junior high schools. Based on the problem and research objectives, this type of research is quasi-experimental. This research was conducted in two groups, namely the learning experiment class using e-modules with a CTL approach and the control class using conventional learning. The population in this study were all seventh-grade students at Blue Junior High School for the 2020/2021 academic year which consisted of 2 classes. To obtain the sample class, namely the experimental and control classes, a random sampling technique was used. VII B was the experimental class, and class VII A was chosen as the control class. The instrument used is a test consisting of 5 questions about conceptual understanding test. Data analysis using the t-test. From the students' responses to the e-module, the criteria were